(untitled) (Scientific journal of the Fergana State University, 2024)
The article proves that the concept of “age” and its division into groups are related not only to biological parameters, but also to social characteristics: the structure of society and culture (at the same time, to language, the linguistic landscape of the world). The complexity of the concept of “age” is clarified by linguistic evidence, as well as the emergence of a large number of terminological combinations used in various scientific fields, for example: biological age, chronological age, somatic age, spiritual age, i.e. human life the inclusion of several age stages is revealed in the case of scientific studies, but their number and precise period boundaries are clarified in the case of conducted studies. “Youth period” forms an ambiguous set of various cultural-historical, social, semiotic, age-related and other factors. All these factors affect the understanding of the “age” structure of society, the specific characteristics of one or another age group, and the attitude that evaluates them. At the same time, there are some stereotypical ideas about age in different linguistic and cultural groups, which are expressed in different national languages, and it is necessary to rely on various types of: lexicographic, textual, discursive sources and experience data in the study of such stereotypical images. studied.